2019
DOI: 10.1002/ijc.32540
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and distress following receipt of results from routine HPV primary testing in cervical screening: The psychological impact of primary screening (PIPS) study

Abstract: We used a cross‐sectional survey to examine short‐term anxiety and distress in women receiving different results following routine human papillomavirus (HPV) primary testing at cervical screening. Participants were women aged 24–65 (n = 1,127) who had attended screening at one of five sites piloting HPV primary screening in England, including a control group with normal cytology who were not tested for HPV. Women completed a postal questionnaire ~2 weeks after receiving their screening result. Unadjusted mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 31 publications
3
93
0
2
Order By: Relevance
“…These findings complement an English study investigating the psychosocial impact of HPV testing on women during piloting of primary HPV testing 26. Anxiety (53.03) and distress (3.94) levels for women who reported testing HPV+ in this study are much higher compared with the English study (women HPV+ with abnormal cytology anxiety 42.9; distress 3.3).…”
Section: Discussionsupporting
confidence: 63%
“…These findings complement an English study investigating the psychosocial impact of HPV testing on women during piloting of primary HPV testing 26. Anxiety (53.03) and distress (3.94) levels for women who reported testing HPV+ in this study are much higher compared with the English study (women HPV+ with abnormal cytology anxiety 42.9; distress 3.3).…”
Section: Discussionsupporting
confidence: 63%
“…Consistently, another study found no differences over a 12-month period (Nagele et al, 2019). General psychological distress (Golderberg & Williams, 1988) was found to be slightly higher (worse) in women testing HPV-positive with abnormal cytology 4-weeks after their result in two studies (Maissi et al, 2004;McBride et al, 2020). However, no differences were found 6-months later in a follow-up study (Maissi et al, 2005) or up to 12 or 24 months later in two other studies (Andreassen et al, 2019;Nagele et al, 2019).…”
Section: Quantitative (Distress)mentioning
confidence: 84%
“…Seventeen papers were quantitative studies (Alay et al, 2019;Andreassen et al, 2019;Ferenidou et al, 2012;Garces-Palacio et al, 2019;Hsu et al, 2018;Kitchener et al, 2008;Kwan et al, 2011;Maggino et al, 2007;Maissi et al, 2004Maissi et al, , 2005McBride et al, 2020;McCaffery et al, 2004;Nagele et al, 2019;Ngu et al, 2018;Rodriguez et al, 2019;Wang et al, 2010;Wang et al, 2011), 15 were qualitative (Barrera-Clavijo et al, 2015;Barreto et al, 2016;Bertram & Magnussen, 2008;Head et al, 2017;Kosenko et al, 2012;Lin et al, 2011;Linde et al, 2019;McCaffery & Irwig, 2005;McCaffery et al, 2006;McCurdy et al, 2011;O'Connor et al, 2014;Perrin et al, 2006;Tiro et al (2019); Waller, McCaffery, et al, 2007;Wyndham-West et al, 2018) and one was mixed-methods (Daley et al, 2010). A total of 12,789 women aged between 18 and 65 participated in twenty studies (n=12,244 quantitative; n=545 qualitative), of whom 4,305 were reported as having tested positive for HPV (n=3,874 quantitative; n=431 qualitative).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations